Pengelolaan Keuangan yang Efektif dan Efisien dalam Meningkatkan Kekuatan Ekonomi bagi Masyarakat Papua dan Papua Barat di Indonesia - Agustinus, John (Jurnal Aplikasi Manajemen, 2016)
Effective financial management is to run all of the financial system in accordance with an agreement in the programming. Public finance management at the local government level provinces of Papua and West Papua are built on the deliberations of local development plans by leveraging Government funds through the General Allocation Fund and Special Autonomy Fund.The use of local government finances governance efficiently and use the funds should be in accordance with the level of achievement of the implementation of the program, so that in implementing all the programs and the use of appropriate financial it will achieve an effective and efficient thefinancial management. This study uses a phenomenological study with Weber's perspective, the data obtained through interviews with the Head of Finance of Papua and West Papua. Besides depth interviews were also conducted Focus Group Discussion together financial experts as lecturers and NGOs. The results showed that the local government financial management is in compliance with the legislation and in the implementation of the program is also in accordance with the plan, it means that the financial management has been effective and efficient in accordance with the program and utilize the funds to the maximum.Â  Â